Exploration of genetic diversity and population structure in North Indian Aegle marmelos accessions using ISSR markers - Prince Minhas; Rajvinder Minhas; Atul Chamyal; Rakesh Kumar; Kanika Aggarwal; Rahul Kumar; Maneet Rana; Vikas Sharma (Ecological Genetics and Genomics, 2026)

Exploring the feasibility and challenges of AI-based rainfall-induced landslides prediction - Dibyajyoti Chutia; Ranjan Kumar Deka; Rahul Kumar; Praveen Kumar; Avinash Chauhan; Puyam S. Singh; Nilay Nishant; Prakash Biswakarma; K. K. Sarma; S. P. Aggarwal (Natural Hazards, 2026)

Review of water treatment technologies for PFAS from a life cycle perspective, with meta-analysis of financial costs and climate impacts - Sabrina Altmeyer Mendes; Rahul Aggarwal; Magdalena Svanström; Gregory Peters (Resources, Conservation and Recycling, 2025)

Extrapolation factors for calculating ecotoxicity effects in LCA - Rahul Aggarwal; Mikael Gustavsson; Gregory Peters; Sverker Molander (The International Journal of Life Cycle Assessment, 2025)
Purpose This study focuses on updating, improving, and expanding the extrapolation factors needed to convert various acute or chronic effect concentration indicators into consistent chronic EC10eq (effect concentration inducing a 10% response over background) for use in life cycle assessment (LCA). Our main objectives include (1) to present a detailed approach for the harmonization of ecotoxicity data, with a focus on deriving extrapolation factors, and (2) to estimate both generic and species group-specific extrapolation factors, facilitating the conversion of effect concentration indicator groups (EC10eq and EC50eq) into chronic EC10eq. Methods Experimental ecotoxicity data were sourced from CompTox Version 2.1.1, which integrates toxicity information from ToxValDB v9.1.1, and the information from REACH registration dossiers. We developed a framework for harmonizing ecotoxicity data, ensuring uniformity and high quality of aquatic ecotoxicity information from these sources. Through linear regression analysis, both generic and species group-specific extrapolation factors were then derived. Results and discussion Harmonization of ecotoxicity data yielded a streamlined dataset with 339,729 datapoints for 10,668 chemicals, reflecting a 54% reduction in raw datapoints. The geometric mean-based aggregation process produced 79,001 aggregated effect concentration datapoints at the species level, 41,303 at the species group level, and 23,215 at the effect concentration indicator level for these chemicals. This process facilitated the derivation of 3 generic and 24 species group-specific extrapolation factors, allowing for the conversion of effect concentration indicator groups (EC10eq and EC50eq) to a chronic EC10eq across two exposure classes (acute vs. chronic) and species groups, as defined in the US EPA ECOTOX knowledgebase, including algae, amphibians, fish, crustaceans, insects/spiders, invertebrates, molluscs, and worms. Conclusions The harmonization of ecotoxicity data and the derived extrapolation factors permit the integration of diverse datapoints with varying effect concentration indicators and exposure durations into USEtox ecotoxicity characterization factors. This has the potential to enhance substance coverage for characterizing ecotoxicity effects across chemicals in LCA frameworks by permitting wider species coverage. More generally, this is part of global efforts to extend the potential for quantitative assessment of environmental impacts of chemicals in an LCA framework.

Freshwater ecotoxicity characterization factors for PMT/vPvM substances - Rahul Aggarwal; Gregory Peters (Chemosphere, 2024)

A numerical study of NOX and soot emissions in ethylene-ammonia diffusion flames with oxygen enrichment - Rahul Suresh; Krishna C. Kalvakala; Suresh K. Aggarwal (Fuel, 2024)

Comparative evaluation of management modules against Maydis leaf blight disease in maize (Zea mays) - Sumit Kumar Aggarwal; K. S. Hooda; Harleen Kaur; Robin Gogoi; Prashant Chauhan; P. K. Bagaria; Pardeep Kumar; Mukesh Choudhary; Rahul Kumar Tiwari; Milan Kumar Lal (European Journal of Plant Pathology, 2024)

A data-driven approach to thermal transmittance (U-factor) calculation of double-glazed windows with or without inert gases between the panes - Damilola Onatayo; Rahul Aggarwal; Ravi S. Srinivasan; Bipin Shah (Energy and Buildings, 2024)

Influence of data selection on aquatic ecotoxicity characterization factors for selected persistent and mobile substances - Rahul Aggarwal; Hanna Holmquist; Rickard Arvidsson; Efstathios Reppas-Chrysovitsinos; Gregory Peters (The International Journal of Life Cycle Assessment, 2024)
Purpose This paper addresses the lack of ecotoxicity characterization factors (CFs) for persistent and mobile (PM) chemicals in life cycle assessment. The specific aims are (1) to provide CFs for 64 selected chemicals and benchmark them against the USEtox database, (2) to propose an ecotoxicity data harmonization strategy, and (3) to analyze the influence of ecotoxicity data sources and data harmonization strategies. Methods Sixty-four per- and polyfluoroalkyl substances (PFAS), triazines, and triazoles were selected. An ecotoxicity data harmonization strategy was developed to ensure data consistency. A screening strategy for including transformation products was also developed. Existing CFs in the USEtox organic substances database (version 2.01) were identified, and new CFs were calculated based on available data sources. The USEtox model (version 2.13) was used for calculations, and the collected ecotoxicity data from different sources were varied to test their influence. Results and discussion The ecotoxicity data harmonization strategy excluded a considerable amount of incompatible data. To the list of 64 chemicals, 3 transformation products were added. Out of the 67 chemicals, experimental ecotoxicity data were available for 47, leading to the use of in silico tools and average values to fill data gaps for 20 chemicals. CFs for 67 chemicals could thus be provided. Comparing CFs calculated based on experimental and estimated ecotoxicity data reveals that the estimated data leads to considerably different CF values. Conclusions The paper provides strategies for ecotoxicity data harmonization and the inclusion of transformation products. The limited availability of experimental ecotoxicity data and differing results of the applied estimation methods highlight the need for further development of estimation methods. In addition, further development in including transformation products is recommended, which is particularly relevant for PM chemicals.

First report of dry rot of potato caused by Fusarium proliferatum in India - Rahul Kumar Tiwari; Bishnu Maya Bashyal; V. Shanmugam; Milan Kumar Lal; Ravinder Kumar; Sanjeev Sharma; Kailash Chandra Naga; Kumar Nishant Chourasia; Rashmi Aggarwal (Journal of Plant Diseases and Protection, 2022)

Snow Cover Area Mapping Using Synthetic Aperture Radar in Manali Watershed of Beas River in the Northwest Himalayas - Praveen K. Thakur; Pradeep K. Garg; Shiv P. Aggarwal; Rahul D. Garg; Sneh Mani (Journal of the Indian Society of Remote Sensing, 2013)